ANALISIS EFEKTIVITAS PENERAPAN INSENTIF PAJAK PMK 44 TAHUN 2020 PADA MASA PANDEMI COVID-19 DALAM UPAYA PEMULIHAN CASH FLOW (Studi Kasus Pada PT.ABC) - Sinta Ustantini; Moh. Amin; Junaidi Junaidi (Universitas Islam Malang, 2021)
The COVID-19 pandemic has a very significant impact on the domestic economy of the nation-state and the existence of MSMEs (Micro, small and medium enterprises). The government has issued incentives and tax facilities that can be utilized by taxpayers. The purpose of this study was to determine the implementation of Minister of finance regulations Number 44 (PMK 44) tax incentives in 2020 during the Covid-19 pandemic, which was effective in efforts to restore cash flow at PT.ABC. This research is a comparative descriptive research type with quantitative calculations by describing comparing the reality and circumstances of an object under study. The implementation of Minister of finance regulations Number 44 (PMK.44) in 2020 can restore PT.ABC’s cash flow supported by an increase in PT.ABC’s profit. However, this recovery is still very ineffective in accordance with the standard measure of effectiveness according to the R&D reference for the Ministry of Home Affairs due to the increase in the final cash balance of 31 December 2020 PT ABC is only by 1.4%.Keyword : Tax Incentives, government born income tax, MSMEs.